2008
DOI: 10.1901/jaba.2008.41-163
|View full text |Cite
|
Sign up to set email alerts
|

Preference for Reinforcers Under Progressive‐ and Fixed‐ratio Schedules: A Comparison of Single and Concurrent Arrangements

Abstract: Progressive-ratio (PR) schedules were used to identify the break point (i.e., the last schedule value completed) for 2 reinforcers under single and concurrent schedules. After the respective break points were established, the same reinforcers were presented under concurrent fixed-ratio (FR) schedules that were yoked to the break points obtained with the PR schedules. Results suggested that the participants responded more for the high-preference item than for the low-preference item, regardless of the presentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 15 publications
1
29
1
Order By: Relevance
“…Previous studies that examined the correspondence between preference and performance on PR schedules generally evaluated only the extreme ends of the preference continuum (Francisco et al, 2008; Glover et al, 2008; Penrod et al, 2008; Roane et al, 2001). In these studies, the reinforcing efficacy of the most preferred stimulus, or high‐ and low‐preference stimuli, was evaluated on PR schedules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies that examined the correspondence between preference and performance on PR schedules generally evaluated only the extreme ends of the preference continuum (Francisco et al, 2008; Glover et al, 2008; Penrod et al, 2008; Roane et al, 2001). In these studies, the reinforcing efficacy of the most preferred stimulus, or high‐ and low‐preference stimuli, was evaluated on PR schedules.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear if all preference assessment formats perform equally well when it comes to the identification of effective reinforcers, as measured by performance on PR schedules. Although some studies have evaluated the correspondence between preference and reinforcer efficacy using PR schedules (e.g., DeLeon et al, 2009; Francisco et al, 2008; Glover, Roane, Kadey, & Grow, 2008; Penrod et al, 2008), most determined preference using PS assessments only. Less is known about how well preference, as measured by other assessment formats that are commonly used in clinical settings, corresponds with reinforcer efficacy, as measured by break points.…”
mentioning
confidence: 99%
“…Participants continue to perform the operant response to obtain a reward before ultimately giving up, presumably because the cumulative effort required to obtain the reward eventually outweighs the perceived value of the reward. Importantly, several studies have validated the human procedures, in which more preferred rewards elicited greater breakpoints than less preferred rewards (Glover et al , 2008; Penrod et al , 2008; Roane et al , 2001; Trosclair-Lasserre et al , 2008). Most studies utilizing progressive ratio reinforcement schedules in humans have done so using drugs of abuse as reinforcers.…”
Section: Translational Assessments Of Reward and Motivationmentioning
confidence: 99%
“…Across all participants, the stimuli selected more often were associated with increased levels of responding (i.e., in-square behavior) relative to stimuli that were selected less often. Likewise, Glover, Roane, Kadey, and Grow (2008) used a combination of progressive-ratio (PR) and fixed-ratio (FR) schedules of reinforcement to compare responding for stimuli that were selected frequently (highly preferred) or infrequently (less preferred) during a preference assessment. The results showed that all participants engaged in more responding (e.g., completing math worksheets) to access the highly preferred stimuli rather than the less preferred stimuli under both PR and FR schedules.…”
mentioning
confidence: 99%